Sales Volume, Operating Cost and its Effect on Profitability (Study on Listed Companies in The Indonesia Stock Exchange (IDX) for 2017-2020) - Padriyansyah Padriyansyah; Ryan Al Rachmat; Trie Sartika Pratiwi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study is associative research that uses more than one independent variable to determine the relationship between the variables studied, namely sales volume, operating costs, and profitability. The data used are in the form of company profit and loss financial statements, which were obtained from the Indonesian stock exchange website www.IDX.co.id. The population used is the annual financial statements published for 4 periods 2017-2020 as many as 16 companies. The sample in this study is in the form of annual financial statements (profit and loss statements) for the 2017-2020 period as many as 10 companies (40 samples) according to the sampling criteria. The results obtained, Sales Volume and Operational Costs affect Profitability as evidenced by the results of Fount 6.827 > Fable of 3.250 with a significant level of 0.003. While partially Sales Volume affects Profitability as evidenced by the results of count of 2,980 and table of 2,026 with a significant value of 0.005, and also Operational Costs affect Profitability as evidenced by a count of -3.599 and table of 2.026 with a significance value of 0.001